Sosialisasi dan Pelatihan Strategi Investasi saat Kondisi Pandemi: Kegiatan Pengabdian Masyarakat kepada Investor Pemula (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2020)
This community service activity aims to provide an understanding of the right investment strategy that can be carried out by novice investors during the pandemic conditions. The method of activity is carried out with the method of socialization assisted by online meeting applications. Prior to the implementation of the activity, a survey was conducted first to determine the condition of the target community. Activity monitoring was done by looking at the implementation of investment activities carried out by the novice investors. The results of the service show that novice investors have understood the investment strategy for pandemic conditions. Based on the results of the post-test, novice investors can determine investment decisions that are appropriate for the pandemic conditions.